Transparent molybdenum sulfide decorated polyaniline complex counter electrodes for efficient bifacial dye-sensitized solar cells. (1st May 2017) - He, Benlin; Zhang, Xin; Zhang, Hongna; Li, Jinyu; Meng, Qi; Tang, Qunwei
Highlights: Aniline-MoS2 complexes are synthesized by a reflux method. PANi-MoS2 complexes are employed as cost-effective and transparent CEs. The incident light from rear side can compensate for the light from anode. The DSSC employing PANi-6 wt‰ MoS2 complex CE shows a bifacial efficiency of 9.71% Abstract: Exploration of cost-effective and transparent counter electrodes (CEs) with high electrocatalytic activity has been a persistent objective of bifacial dye-sensitized solar cells (DSSCs) development. Here, with an aim of accelerating charge transfer and increasing the active sites of a transparent CE, molybdenum sulfide (MoS2 ) decorated aniline complexes are synthesized by a reflux technique and subsequently in-situ polymerized for transparent polyaniline (PANi)-MoS2 complex CEs for efficient bifacial DSSCs. The preliminary results indicate that the electrocatalytic activity toward I3 − reduction of PANi-MoS2 complex CE is dramatically enhanced due to the fast charge transfer between PANi (N atoms) and MoS2 (Mo atoms) by the metal (dπ)-nitrogen (pπ) antibonding interaction. Owing to the high optical transparency, electrocatalytic reduction toward I3 − species, superior charge-transfer ability for I − /I3 − redox couples, the bifacial DSSCs based on PANi-6 wt‰ MoS2 complexes CE yield a maximum power conversion efficiency of 7.99% from front irradiation, 3.40% from rear irradiation and 9.71% from both irradiation, which are higher than front, rear and both efficiencies of 6.37%, 1.78% and 7.50% for DSSC employing PANi CE, respectively. The high optical transparency and electrocatalytic activity along with simple preparation, relatively low cost and scalability demonstrate the potential use of PANi-MoS2 complex as a robust CE in bifacial DSSCs.